Changes in chemical composition of drilling waste water in taiga zone of Western Siberia (the Russian Federation) on the basis of thermodynamic approach; IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Savichev O. G. Oleg Gennadievich (Hydrogeochemistry and Hydrogeoecology, 2016)
Title screen